Security-Aware and Privacy-Preserving D2D Communications in 5G - Zhang, Aiqing; Lin, Xiaodong (IEEE network, 2017)
Device-to-device communication is a promising technology that can offload heavy traffic in 5G networks. However, due to its open nature, there are several security issues. The LTE-A standard introduces security and protection mechanisms, which include mutual authentication between the UEs and the eNB. Unfortunately, D2D communications still face various threats: jamming, data modification, free-riding, and privacy violation. In this article, we first give an architecture for an LTE-D2D system and its application scenarios with various security threats and requirements. Then we investigate privacy concerns in terms of location privacy, identity privacy, and data privacy. Afterward, we propose security solutions from aspects of application-layer security and physical-layer security, respectively. Further, we propose two frameworks for cross-application-physical-layer security methods. Finally, the challenges and future research directions are presented.